Book yourself solid the fastest, easiest, and most reliable system for getting more clients than you can handle even if you hate marketing and selling - Port, Michael 1970- (Wiley, 2013)
A visual way to easily access the strategies and tactics in Book Yourself Solid Learning new concepts is easier when you can see the solution. Book Yourself Solid Illustrated, a remarkable, one-of-a-kind work of art, transforms the Book Yourself Solid system into a more compelling and easy-to-consume playbook for any business owner. You won't find business school graphs or mind maps. Instead, you'll find compelling, visual stories that reinvent old and tired business concepts, making Book Yourself Solid Illustrated a fun and playful book that y.